Bismuth-modified vanadyl pyrophosphate catalysts - Taufiq-Yap, Y.H.; Tan, K.P.; Waugh, K.C.; Hussein, M.Z.; Ramli, I.; Abdul Rahman, M.B. (Springer, 2003)
Vanadium phosphorous oxide (VPO) is the commercial catalyst for the selective oxidation of butane to maleic anhydride. A 1% bismuth-doped VPO catalyst was prepared by refluxing Bi(NO3)3 and VOPO4·2H2O in isobutanol (denoted as VPD). Bismuth incorporation into the VPO lattice lowered the overall V oxidation state from 4.24 to 4.08. It lowered the peak maximum temperature for the desorption of oxygen from the lattice from 100.1 K (undoped) to 964 K with a shoulder at 912 K and the peak maxima for H2 TPR from 863, 1011, and 1143 K (undoped) to 798, 906, and 1151 K. The total oxygen desorbed from the Bi-doped catalyst was only one-fourth that of the undoped catalyst, while the amount of oxygen removed by TPR was roughly the same for both catalysts. In anaerobic oxidation, the Bi-doped catalyst had roughly the same activity as in undoped catalyst in C4 hydrocarbon oxidation but had a higher selectivity to products such as olefins and maleic anhydride. The undoped VPD catalyst showed a rosette-type structure with a crystallite of uniform size. However, Bi-doped catalyst exhibited more layered platelike crystals, which form at the surface of clusters.